A day in the life of a forensic paramedic. (2nd October 2021) - Moore, Angela
Abstract : In this month's instalment of Paramedic Roles, Angela Moore provides an insight into the role of a forensic paramedic, with a brief run-down of her daily responsibilities, as well as a reflection on her overall motivation